Feeling at Home in the Wilderness: Environmental Conditions, Well-Being and Aesthetic Experience - Løvoll, Helga Synnevåg; Sæther, Knut-Willy; Graves, Mark (Frontiers in Psychology, 2020)
Environmental conditions affect one’s aesthetic experience in natural environments. Understanding that effect requires accounting for the conditions affecting one’s attention and experience. Rather than attempt to reduce and control environmental factors, we compare two similar groups during naturally occurring, intense and overwhelming conditions and examine the relationship between common characteristics as well as environment and group differences. Participants undertook a five-day, winter, wilderness adventure training course designed to challenge their considerable wilderness and leadership skills under two different extreme weather conditions but within the same wilderness area (n=47 full participation). In addition to pre- and post-adventure questionnaires, participants responded daily during the wilderness experience to briefly describe a self-selected, strong experience of nature; characterize its associated feeling states; and answer questions probing eight aesthetic aspects of the experience. Participant strong experience of nature related to hedonic and eudaimonic feelings in different ways depending upon environmental conditions. In particular, strong correlations occurred between agreement ratings with “I felt at home in nature” daily experience reports and satisfaction with life and personal growth trait measures, but primarily during sunny and cold conditions on a high plateau (PG: Pearson r=.51; SWL: r=.70) and not significantly in stormy and wet weather in a mountain forest. In addition, experience narratives that correspond to strongest agreement to feeling at home in nature were examined for shared themes and synthesized into six dimensions: focus on sensory experiences at a particular moment, self-reflection, wonder, appreciation of beauty, positive emotions, and insight of relation to nature. These findings actualize the notion of wonder, aroused by sudden feelings or by reflection, as a salient ingredient in feeling at home in wilderness. The finding of feeling at home in nature, as the most important feature relating to feelings and well-being, is discussed in relation to self-awareness, philosophical thinking, and potential ethical awareness.